Political leadership themes, contexts, and critiques - Foley, Michael 1948- (Oxford University Press, 2014)
Despite its recognized significance in social life, leadership is a notoriously elusive subject that generates a host of different points of explanatory focus. This is particularly so in the field of political leadership, which has been afflicted by an enduring split between the biographical idiosyncrasies of individual leaders and the specialist contributions from an array of social science disciplines. This new study is designed to establish an improved balance between this often myopic and confusing bifurcation of approaches.